2020
DOI: 10.1108/nfs-01-2020-0005
|View full text |Cite
|
Sign up to set email alerts
|

Tempeh and red ginger flour for hypercholesterolemic rats

Abstract: Purpose This study aims to evaluate the effect of the combination of tempeh and red ginger flour in hypercholesterolemic rats. Design/methodology/approach Sprague Dawley male rats (n = 30; body weight 150-200 g) were randomly divided by five groups (n = 6), consist of negative control (K−) group: group fed by normal diet (laboratory standard diet laboratory, 4.35 kcal/g, 0% cholesterol); positive control (K+) group: group fed by high cholesterol diet (5.28 kcal/g, 12.1% cholesterol); Treatment 1 (P1) group: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
1
0
1
Order By: Relevance
“…At the moment, Qureshi et al (2010) demonstrated that by the augmentation of ginger powder on daily basis the insulin activity can be increased up to 4%. Contemporary, Dewi et al (2021) concluded that ginger owing to its nutraceutic potential has a pharmacological impact on metabolic syndromes mainly against cancer, inflammation, apoptosis, lipid profile and diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
“…At the moment, Qureshi et al (2010) demonstrated that by the augmentation of ginger powder on daily basis the insulin activity can be increased up to 4%. Contemporary, Dewi et al (2021) concluded that ginger owing to its nutraceutic potential has a pharmacological impact on metabolic syndromes mainly against cancer, inflammation, apoptosis, lipid profile and diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
“…Kelebihan ROS dapat merusak struktur sel seluler (protein, lipid dan DNA). Kerusakan peroksidasi lipid, dan oksidatif lipid menghasilkan produk aldehid reaktif seperti MDA (Valko et al, 2007) , (Dewi et al, 2020). MDA memiliki kemampuan reaksi yang reaktif secara kovalen dengan makromolekul terutama protein (Akinola et al, 2010;Gourine et al, 2018).…”
Section: Pendahuluanunclassified